Sytematic Literature Review : Assessing the Effectiveness of Performance-Based Budgeting in Government Financial Management - Megah S, Karina Indri; Valiant S, Roy (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
This systematic literature review (SLR) examines the impact of Performance-Based Budgeting (PBB) on public financial management in Indonesia, emphasizing efficiency, accountability, and transparency. The study aims to identify key obstacles and factors affecting the success of PBB implementation while drawing lessons from international experiences, particularly from Ukraine, the United States, Colombia, and Chile. The research synthesizes literature from various academic sources, including Scopus-indexed journal articles, and employs a qualitative approach with Vosviewer to analyze 60 relevant studies. Findings indicate that PBB in Indonesia has yet to significantly enhance financial management due to persistent challenges such as poor data quality, inadequate institutional capacity, and political resistance. Although some progress has been observed, these barriers continue to limit PBB’s effectiveness. Comparative case studies suggest that successful implementation requires strong political will, improved data infrastructure, institutional strengthening, and active public participation. The study concludes that while PBB has the potential to enhance financial management, its full realization in Indonesia depends on overcoming these challenges. However, limitations exist, particularly the reliance on secondary data and the absence of empirical research on local governments. Future studies incorporating primary data collection are recommended to gain deeper insights into practical issues and potential solutions for PBB implementation at the local level.